The Effects of Installation Faults of Air Conditioning Systems on Carbon Emissions - Ergen, Ruveyda; Gürtürk, Mert (My University, 2025)
In this study, the effects of installation faults of condenser of Air Conditioning (AC) systems on emissions were investigated and Life Cycle Climate Performance (LCCP) analysis was carried out according to the scenario of installation faults of the condenser unit of the AC system for 12 countries. The heat taken by the evaporator units of the ACs is transferred to the condenser unit via the system. This thermal energy is transferred to the surrounding air via condenser. The surrounding air cannot pass through the condenser unit in desired amounts and causes more electricity consumption of the system due to installation faults. The rates of increase of the LCCP values change from 0.02% to 29.6% because of installation faults. The LCCP value was calculated as 19692 – 19858 kg?CO2e with the closing of the air inlet because of installation faults for Turkey. Considering the installation faults of the condenser, the LCCP value was calculated as 21284 - 21505 kg?CO2e for Japan.
Keywords: Emissions; Global Warming; LCCP; Air-conditioning